Evaluating the effects of a classroom-based bicycle education intervention on bicycle activity, self-efficacy, personal safety, knowledge, and mode choice - Nachman, Elizabeth R.; Rodriguez, Daniel A. (Frontiers in Sustainable Cities, 2023)
This study provides an evaluation of the impacts of classroom-based adult bicycle education on bicycling activity, confidence and competency self-perceptions while bicycling, knowledge of the bicycling rules of the road, and mode choice in a sample of residents of the San Francisco Bay Area in the US. Changes were measured with self-administered surveys completed before and again six weeks after the course intervention. Self-reported data were validated using objective data collected using the Ride Report app. Participants reported statistically significant increases in confidence while bicycling in both traffic and car-free areas, feelings of safety while bicycling in car-free areas, and knowledge of the rules of the road. Although overall changes in bicycling activity did not change, participants with initial low confidence increased bicycling activity and feelings of safety in traffic, compared to participants overall. Classroom-based bicycle education courses can improve bicycling confidence self-perception and increase knowledge of the bicycling rules of the road.